2022
DOI: 10.1080/19420862.2022.2073632
|View full text |Cite
|
Sign up to set email alerts
|

An adapted consensus protein design strategy for identifying globally optimal biotherapeutics

Abstract: Biotherapeutic optimization, whether to improve general properties or to engineer specific attributes, is a time-consuming process with uncertain outcomes. Conversely, Consensus Protein Design has been shown to be a viable approach to enhance protein stability while retaining function. In adapting this method for a more limited number of protein sequences, we studied 21 consensus single-point variants from eight publicly available CD3 binding sequences with high similarity but diverse biophysical and pharmacol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Another important factor is the stability of the BsAbs containing scFv in serum and PBS. 36 To determine the serum stability of the three BsAbs, they were incubated in 90% mouse serum or in PBS, and their degradation over time was monitored by their binding to the target antigen(s). The data indicated that neither incubation in mouse serum nor in PBS in a time course over 4 d resulted in a loss of binding, suggesting that all molecules were stable (Table S3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important factor is the stability of the BsAbs containing scFv in serum and PBS. 36 To determine the serum stability of the three BsAbs, they were incubated in 90% mouse serum or in PBS, and their degradation over time was monitored by their binding to the target antigen(s). The data indicated that neither incubation in mouse serum nor in PBS in a time course over 4 d resulted in a loss of binding, suggesting that all molecules were stable (Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…The bispecific antibodies IgG1-scFv investigated in this study were produced in-house by mammalian cell culture technology using CHO cells and purified with a standard procedure as described previously. 36 All bispecific antibodies are similar in size with a molecular weight between 195 and 205 kDa. Sample quality was ensured by quantification using analytical size exclusion chromatography passing the acceptance criteria (>97%).…”
Section: Methodsmentioning
confidence: 99%
“…Ahmed et al previously showed, through sequence and structural analysis, that non-redundant physicochemical descriptors can be used to flag Fv regions of antibodies for medicine-likeness. 203 There are numerous ways computer-aided drug design can contribute to the marketed antibody-based biotherapeutic landscape, 204 including sequence analysis (for example, see Figures S3 (a, b)), 205 structure analysis, 206 and machine learning. 207 …”
Section: Discussionmentioning
confidence: 99%
“…In order to determine the % monomer of the multispecific antibodies, analytical size exclusion chromatography was carried out using the Agilent HPLC system as previously described 22 . 10&g of sample were injected onto two tandemly connected Acquity BEH200 columns (Waters, 1.7 &m, 4.6 X 150 mm) at a flow rate of 0.25 mL/min.…”
Section: Experimental Setup For Antibody Production and Characterizationmentioning
confidence: 99%
“…All multispecific antibodies were expressed from transfected Chinese hamster ovary (CHO) cells and expressed and purified using Protein A chromatography as previously described 21 .…”
Section: Multispecific Antibody Expression and Purificationmentioning
confidence: 99%